SPIRITUAL SPACE OF SOCIETY AND THE INDIVIDUAL: PRESENTATION AND PERCEPTION - Сідоркіна, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article discusses the features of perception of spiritual space in the collective consciousness, conceptions of its main elements.